TERMINOLOGI TEKNOLOGI PEMBELAJARAN: Suatu Tinjauan Historis - Yaumi, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2016)
This article aims at analyzing the terminology of instructional technology from the historical perspectives. The development of the terms impacts the nomenclature, role, domain, and the object of the study. The term instructional technology is perceived the same as educational technology by some experts, while some others considered different. Technology is the application of knowledge for practical purposes. In early development, instructional technology was seen as instructional media, and then it was considered as a science, process, which includes the field of design, development, utilization, management, and evaluation of processes and learning resources, and currently is focused on facilitating learning and improving performance.